Possible contamination of the intergalactic medium damping wing in ULAS J1342+0928 by proximate damped Lyα absorption - Davies, Frederick B.; Bañados, Eduardo; Hennawi, Joseph F.; Bosman, Sarah (The astrophysical journal. Part 2, Letters, 2025)
The red damping wing from neutral hydrogen in the intergalactic medium is a key predicted signature of ongoing reionization. One potential contaminant of the intergalactic damping wing signal is dense gas associated with foreground galaxies, which can give rise to proximate damped Lyα absorbers. The Lyα imprint of such absorbers on background quasars is indistinguishable from the intergalactic medium within the uncertainty of the intrinsic quasar continuum, and their abundance at z ≳ 7 is unknown. Here we show that the complex of low-ionization metal absorption systems recently discovered by deep JWST/NIRSpec observations in the foreground of the z = 7.54 quasar ULAS J1342+0928 can potentially reproduce the quasar’s spectral profile close to rest-frame Lyα without invoking a substantial contribution from the intergalactic medium, but only if the absorbing gas is extremely metal-poor ([O/H] ∼ −3.5). Such a low oxygen abundance has never been observed in a damped Lyα absorber at any redshift, but this possibility still complicates the interpretation of the spectrum. Our analysis highlights the need for deep spectroscopy of high-redshift quasars with JWST or the Extremely Large Telescope to “purify” damping wing quasar samples, an exercise that is impossible for much fainter objects like galaxies.
Veröffentlicht: 11. August 2025
Gesehen am 20.01.2026